Pressure effect on magnetic susceptibility and exchange interactions in GdMx (x = 1, 2, 3, 5) systems - Grechnev, G.E.; Panfilov, A.S.; Baranovskiy, A.E.; Logosha, A.V.; Svechkarev, I.V. (Физика и техника высоких давлений, 2004)
Effect of pressure on electronic structure and magnetic properties of GdMx (x = 1, 2, 3, 5) systems is studied experimentally and theoretically. By employing the ab initio electronic structure calculations, the magnetic susceptibilities, saturation moments, exchange parameters, magnetic ordering temperature and their pressure derivatives are evaluated and appeared to be consistent with available experimental data. The obtained results are expected to promote further advance in the theory of magnetic ordering in rare-earth systems.